Factors Influencing General Science Performance of Female Students in Grade 7 at Rimeti Primary School, West Harerge, Ethiopia - Ashenafi Taye Negewo; Belay Sitotaw Goshu; Muhammad Ridwan (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2026)
This study explores the impact of teacher practices and classroom dynamics on the science performance of 75 Grade 7 female students at Rimeti Primary School, conducted in July 2024/25. Utilizing a two-way ANOVA on simulated test score data, the research assessed the effects of interactive versus traditional teaching methods and collaborative versus competitive classroom environments. Results revealed significant main effects for teacher practices (F (1, 96) = 30.56, p = 2.78e-07), with interactive methods yielding higher mean scores (72.15) compared to traditional methods (61.95), and classroom dynamics (F (1, 96) = 18.12, p = 4.82e-05), where collaborative settings outperformed competitive ones. The interaction effect was non-significant (F (1, 96) = 0.02, p = 0.885), indicating independent contributions. A box plot visually confirmed these trends, showing elevated medians for Interactive/Collaborative groups. These findings suggest that interactive teaching and collaborative dynamics independently enhance science achievement, with teacher practices explaining greater variance (1621.66 sums of squares) than dynamics (961.69). Limitations include the use of simulated data and a single-gender focus, restricting generalizability. The study aligns with social constructivist and cooperative learning theories, advocating for pedagogical innovation in under-resourced settings. Recommendations include teacher training in interactive methods and fostering collaborative classrooms, supported by resource allocation and further longitudinal research. This research provides a foundation for improving science education for female students in similar contexts.